Application of electromagnetism method to characterize the degradation behavior in structural mild steel within the elastic range. (30th April 2020) - Wang, Xiao; Chen, Jian-Guo; Su, Guo-feng; Cui, Chong; Li, Hua-Ying
Highlights: Early degradation of structural steel was investigated for integrity assessment. Evolution of dislocation structure in mild steel within the elasticity was revealed. Magnetic technique was employed to characterize the degradation of structural steel. Effect of early degradation on the magnetic property of mild steel was investigated. Abstract: This paper reports a novel use of magnetic technique to characterize the degradation in mild steel within the elastic range. Firstly, the mild steel specimens were stretched to several different kinds of stress within the elasticity. After the tensile test, a shift of hysteresis loop was observed in the tensile specimen, and the variations of magnetic parameters such as Coercivity ( H c ), Remanence ( B r ), maximum permeability (µm ), and hysteresis loop area ( S ) were also evident. When the tensile stress increases to the elastic limit (310 MPa), the H c increased 16.44% compared with the original specimen, which manifested the variation of the magnetic property in mild steel. The magnetic property variation in material are closely interrelated with its microstructure change. The existence of internal residual stress/strain as well as the dislocation structure change are the main factors affect the magnetic property. The experiment results revealed that the magnetic technique was sensitive to the microstructural change in the mild steel, which has the promising potential to characterize the material degradation at the early stage.